Evaluation of radical radiotherapy tolerance in breast cancer patients over 75 - Kleszyk, Łukasz; Urbańczyk, Hubert (Menopause Review/Przegląd Menopauzalny, 2012)
Introduce and aim of the study : A common problem during radiotherapy of breast cancer patients, is both early (mainly skin reactions) and late (occuring withing months to years after treatment completion) normal tissue toxicity. This study aims to evaluate the tolerance of radical radiotherapy in patients with breast cancer aged over 75 years. Material and methods : Retrospective analysis was performed on a group of 44 patients over 75 (ranging from 75 to 85 years old, median 77 years), treated with radical radiotherapy to the chest wall, in Maria Skłodowska-Curie Memorial Cancer Center and Institute of Oncology in Gliwice between 2008 and 2009. Surgical treatment was performed in 42 patients (95,5%). A breast amputation was performaed in 37 patients, 5 patients had undergone breast conserving surgery (BCT). Two patients were treated with radiotherapy alone. Total dose ranged from 44 to 70 Gy with a median of 50 Gy. Fractional dose ranged from 2 to 2.5 Gy (median 2 Gy). Most patients (75%) also received radiotherapy to supraclavicular and axillar lymph nodes. Total treatment time ranged from 21 to 67 days (median 35 days). Toxicity was assessed using the EORTC / RTOG scale, statistical analysis was performed using descriptive statistics in Statistica. Results : Acute skin toxicity was noted in 41 (93%) patients, the majority (78%) presented grade I effects. 10% and 12% of all patients presented respectively grade II and III effects and their occurrence was related closely to the total dose escalation. Median time for an acute skin reaction to occur was 23 days (ranging from 10 to 50 days). Acute grade I hematologic toxicity (anemia, leucopenia, thrombocytopenia) was diagnosed in 8 (18%) patients, occuring between 17 and 83 (median 47,5) days from the start of the treatment. Late grade I pulmonary toxicity (sporadic exertional dyspnea) was reported in one patient, occuring 202 days after completion of the treatment. One patient required a break during radiotherapy, 5 patients (11.5%) had the total dose reduced due to increased skin toxicity Conclusions : Modern radiotherapy is a safe and well tolerated method of radical breast cancer treatment, whether adjuvant or alone, which is especially important in elderly patients disqualified from surgical and/or systemic treatment.